An exploratory study of whether pregnancy outcomes influence maternal self-reported history of child maltreatment. (November 2018) - Cammack, Alison L.; Hogue, Carol J.; Drews-Botsch, Carolyn D.; Kramer, Michael R.; Pearce, Brad D.; Knight, Bettina; Stowe, Zachary N.; Newport, D. Jeffrey
Abstract: Childhood maltreatment is common and has been increasingly studied in relation to perinatal outcomes. While retrospective self-report is convenient to use in studies assessing the impact of maltreatment on perinatal outcomes, it may be vulnerable to bias. We assessed bias in reporting of maltreatment with respect to women's experiences of adverse perinatal outcomes in a cohort of 230 women enrolled in studies of maternal mental illness. Each woman provided a self-reported history of childhood maltreatment via the Childhood Trauma Questionnaire at two time points: 1) the preconception or prenatal period and 2) the postpartum period. While most women's reports of maltreatment agreed, there was less agreement for physical neglect among women experiencing adverse perinatal outcomes. Further, among women who discrepantly reported maltreatment, those experiencing adverse pregnancy outcomes tended to report physical neglect after delivery but not before, and associations between physical neglect measured after delivery and adverse pregnancy outcomes were larger than associations that assessed physical neglect before delivery. There were larger associations between post-delivery measured maltreatment and perinatal outcomes among women who had not previously been pregnant and in those with higher postpartum depressive symptoms. Although additional larger studies in the general population are necessary to replicate these findings, they suggest retrospective reporting of childhood maltreatment, namely physical neglect, may be prone to systematic differential recall bias with respect to perinatal outcomes. Measures of childhood maltreatment reported before delivery may be needed to validly estimate associations between maternal exposure to childhood physical neglect and perinatal outcomes.